Pelaksanaan Pendidikan Agama Pada SD-LB B Sidakarya Kota Denpasar - Mulyani Mudis Taruna (Analisa: Journal of Social Science and Religion, 2010)
The  Research  on the Implementation of Religious Education was conductedat the  SD Luar Biasa Part  B (SD-LB B) Sidakarya Denpasar, Bali  Province. Theresults of this study indicate that the religious education implementation at theSD-LB B Sidakarya is still less attention. It can be seen from  the teaching materials that still use the public school textbook and there is no RPP or specialized reference books for SD-LB B, religious teachers concerns to a religion teacher. The supporting factors in the process of learning  is  good  spirit for student availability of classrooms, school infrastructure and the location is not far from the student  environment.  The problem Inhibiting in the  learning    rocess is the lack of teaching tools, no specific reference books for  deaf and dumb there isnt good attantion for religioous teaching is still not getting  the attention of the series.